2018
DOI: 10.1051/matecconf/201816807016
|View full text |Cite
|
Sign up to set email alerts
|

Impact of oxygen enhanced combustion of natural gas on thermal efficiency of combustion aggregate

Abstract: The aim of the present article is to present the achieved results on the experimental combustion aggregate. In the experimental measurement, the increased of the oxygen concentration in the oxidizing agent in the combustion of natural gas has been used. The results presented in this article are focused to achieve the thermal efficiency of the device, which is expressed by useful heat of the combustion aggregate. Part of the article is the analysis of the heating heat exchanger based on heat flow by convection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Often, an increase in the production capacity and plant flexibility is also pursued [32,33]. Considering these goals, several approaches can be adopted, including: -Fuel switch to cleaner and/or cheaper one, often retrofitting fossil fuel boiler to (co-) combustion of natural gas [34], process gases [35], biomass [36,37] or waste fuels [38,39]; -Refitting the existing boilers to oxycombustion [40], which requires installation of an air separation unit for oxygen-enriched air production [41,42] improving fuel burnout, cuts down greenhouse gases emissions [43,44], and can be a pre-requisite to carbon capture from flue gas [45,46]; -Supplementing the existing boilers with a gasification unit [47,48], enabling processing of a wide range of even low-quality materials into combustible gas [49,50]; -Adding a "topping" unit to the existing Rankine cycle unit, usually a gas turbine [51,52], internal combustion engine [53] or a battery of fuel cells [32], resulting in multiple variants of modified plant layout [54]. Each of those variants results in layout reorganization of the remaining plant parts, usually including changes in boiler feedwater train [55,56], boiler air and flue gas fans, and in flue gas and ash handling equipment [57] to boost the energy efficiency even further and to meet the tightening limits of pollutant emissions set by legislation [58].…”
Section: Repowering Of Thermal Power Plants and Industrialmentioning
confidence: 99%
“…Often, an increase in the production capacity and plant flexibility is also pursued [32,33]. Considering these goals, several approaches can be adopted, including: -Fuel switch to cleaner and/or cheaper one, often retrofitting fossil fuel boiler to (co-) combustion of natural gas [34], process gases [35], biomass [36,37] or waste fuels [38,39]; -Refitting the existing boilers to oxycombustion [40], which requires installation of an air separation unit for oxygen-enriched air production [41,42] improving fuel burnout, cuts down greenhouse gases emissions [43,44], and can be a pre-requisite to carbon capture from flue gas [45,46]; -Supplementing the existing boilers with a gasification unit [47,48], enabling processing of a wide range of even low-quality materials into combustible gas [49,50]; -Adding a "topping" unit to the existing Rankine cycle unit, usually a gas turbine [51,52], internal combustion engine [53] or a battery of fuel cells [32], resulting in multiple variants of modified plant layout [54]. Each of those variants results in layout reorganization of the remaining plant parts, usually including changes in boiler feedwater train [55,56], boiler air and flue gas fans, and in flue gas and ash handling equipment [57] to boost the energy efficiency even further and to meet the tightening limits of pollutant emissions set by legislation [58].…”
Section: Repowering Of Thermal Power Plants and Industrialmentioning
confidence: 99%
“…burners and, as a consequence, can be employed in various combustion systems [6]. Previous studies have suggested that Lowlevel oxygen enrichment not only costs less among these three enhancement regimes, but has also a positive impact on heating rate increase and fuel saving [3] and efficiency [9] in furnaces, fuel consumption and flue gases reduction in a gas turbine [10], thermal efficiency increase and fuel consumption and unburned hydrocarbons decrease in a diesel engine [11], and a higher combustion efficiency in a combustion chamber with heat exchanger [12]. In such circumstances, noise level will play an important role in the feasibility of using low-level oxygen enhanced systems in burners while it has not been yet addressed in low level OEC or combustion noise studies.…”
Section: Introductionmentioning
confidence: 99%